"I'm not going to lay back and watch somebody die": a qualitative study of how people who use drugs' naloxone experiences are shaped by rural risk environment and overdose education/naloxone distribution intervention - Zora Kesich; Umedjon Ibragimov; Kelli Komro; Kenneth Lane; Melvin Livingston; April Young; Hannah L. F. Cooper (BMC, 2023)
Abstract Background Overdoses have surged in rural areas in the U.S. and globally for years, but harm reduction interventions have lagged. Overdose education and naloxone distribution (OEND) programs reduce overdose mortality, but little is known about people who use drugs' (PWUD) experience with these interventions in rural areas. Here, we analyze qualitative data with rural PWUD to learn about participants' experiences with an OEND intervention, and about how participants' perceptions of their rural risk environments influenced the interventions' effects. Methods Twenty-nine one-on-one, semi-structured qualitative interviews were conducted with rural PWUD engaged in the CARE2HOPE OEND intervention in Appalachian Kentucky. Interviews were conducted via Zoom, audio-recorded, and transcribed verbatim. Thematic analysis was conducted, guided by the Rural Risk Environment Framework. Results Participants' naloxone experiences were shaped by all domains of their rural risk environments. The OEND intervention transformed participants' roles locally, so they became an essential component of the local rural healthcare environment. The intervention provided access to naloxone and information, thereby increasing PWUDs' confidence in naloxone administration. Through the intervention, over half of participants gained knowledge on naloxone (access points, administration technique) and on the criminal-legal environment as it pertained to naloxone. Most participants opted to accept and carry naloxone, citing factors related to the social environment (responsibility to their community) and physical/healthcare environments (overdose prevalence, suboptimal emergency response systems). Over half of participants described recent experiences administering intervention-provided naloxone. These experiences were shaped by features of the local rural social environment (anticipated negative reaction from recipients, prior naloxone conversations). Conclusions By providing naloxone paired with non-stigmatizing health and policy information, the OEND intervention offered support that allowed participants to become a part of the healthcare environment. Findings highlight need for more OEND interventions; outreach to rural PWUD on local policy that impacts them; tailored strategies to help rural PWUD engage in productive dialogue with peers about naloxone and navigate interpersonal conflict associated with overdose reversal; and opportunities for rural PWUD to formally participate in emergency response systems as peer overdose responders. Trial registration The ClinicalTrials.gov ID for the CARE2HOPE intervention is NCT04134767. The registration date was October 19th, 2019.